THE EFFECT OF EMPLOYEE PERFORMANCE AND WORK MOTIVATION ON WORK QUALITY DURING THE COVID-19 PANDEMIC PERIOD AT VICTORY PLUS SCHOOL - Sudiantini, Dian (Universitas Pelita Harapan, 2022)
This study aims to analyze empirically the Effect of Employee Performance and Work Motivation During the Covid-19 Pandemic Period at Victory Plus School. The population in this study were employees who worked at the Victory Plus School. And the sample of this study was 80 respondents using the Simple Random Sampling method which is a random sampling of members of the population without regard to the existing strata in the population. The analysis in this study uses multiple linear analysis. The results showed that the results of the t test, employee performance variables and work motivation had a significant effect on work quality.